2018
DOI: 10.3390/pharmacy6030101
|View full text |Cite
|
Sign up to set email alerts
|

A National Survey of Community Pharmacists on Smoking Cessation Services in Thailand

Abstract: Providing smoking cessation services is one role of community pharmacists in Thailand. This cross-sectional study aimed to investigate activities and barriers related to smoking cessation services provided in community pharmacies in Thailand, as well as to compare these activities and barriers between those pharmacists providing and those not providing smoking cessation services. A postal questionnaire was conducted to collect information from community pharmacists across Thailand. In all, 413 valid responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…Moreover, pharmacists reported lack of time as one of the challenges that they experienced when following-up patients. This is consistent with the findings of previous studies where pharmacists reported lack of time, understaffing, and busy schedules as barriers to providing smoking cessation services [29][30][31][32].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, pharmacists reported lack of time as one of the challenges that they experienced when following-up patients. This is consistent with the findings of previous studies where pharmacists reported lack of time, understaffing, and busy schedules as barriers to providing smoking cessation services [29][30][31][32].…”
Section: Discussionsupporting
confidence: 92%
“…Studies on smoking cessation methods among young adult smokers remain limited. Even though community pharmacist counseling on smoking cessation was deemed effective as an intervention recommended in several national guidelines [12,13], most counseling clients were either elderly subjects with chronic diseases or prone to experiencing health problems and a scalability of smoking cessation counseling provided in community pharmacy is still limited [14]. Interactive health education tools available on smartphone apps have demonstrated increase knowledge, skills, and self-efficacy levels among patients with various health conditions, including smoking cessation [15].…”
Section: Introductionmentioning
confidence: 99%
“…This was also described in-depth in the Chinwong and Chinwong study. [ 20 ] In-depth relationship between CPs and patients is important to enhance the role of CPs in CVD prevention. Notably, CPs believe that Cypriots do not acknowledge them as an advisor; a fact that possibly prevent CPs from having an active role in CVD prevention.…”
Section: Discussionmentioning
confidence: 99%
“…CPs expressed their interest in screening programs, with a main one the hypertension screening-related intervention. [ 22 ] In addition, Greek pharmacists after structure training[ 20 ] already delivered successfully the first pharmacy-led WM program followed by an evaluation of it with both service providers and receivers. [ 23 ] However, pharmacists from Cyprus, Greece, and the UK expressed a need for support from the MoH in order to achieve their needs.…”
Section: Discussionmentioning
confidence: 99%